2017
DOI: 10.1039/c7cy00547d
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-supporting hollandite-type vanadium–chromium mixed oxides as efficient heterogeneous catalysts for deoxygenation of sulfoxides under atmospheric H2 pressure

Abstract: In the presence of hollandite-based catalysts, various sulfoxides and pyridine N-oxides could be converted into deoxygenated products under atmospheric H2 pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Among Pt NP catalysts supported on metal oxides (the metal loading was fixed to be 0.5 wt %), Pt/H x MoO 3−y exhibited the highest catalytic activity, affording diphenyl sulfide (2) in >99% yield in 7 h of reaction (Figure 3a), corresponding to a turnover number (TON) of 160 with respect to the total number of Pt atoms in the catalyst. Considering the reaction conditions implemented in this study, this value is superior to those obtained with previously reported catalysts requiring high temperature and high H 2 pressure (Pd/C: TON 50 (at 90 °C, 79 atm); 39 Pt/V (1−x) Cr x -Hol: TON 230 (at 100 °C, 1 atm); 41 Ru/TiO 2 : TON 500 (at 100 °C, 1 atm) 42 ). In fact, Pd/C (5% Pd) catalyst 39 was totally inactive in this reaction under the conditions implemented in this study.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Among Pt NP catalysts supported on metal oxides (the metal loading was fixed to be 0.5 wt %), Pt/H x MoO 3−y exhibited the highest catalytic activity, affording diphenyl sulfide (2) in >99% yield in 7 h of reaction (Figure 3a), corresponding to a turnover number (TON) of 160 with respect to the total number of Pt atoms in the catalyst. Considering the reaction conditions implemented in this study, this value is superior to those obtained with previously reported catalysts requiring high temperature and high H 2 pressure (Pd/C: TON 50 (at 90 °C, 79 atm); 39 Pt/V (1−x) Cr x -Hol: TON 230 (at 100 °C, 1 atm); 41 Ru/TiO 2 : TON 500 (at 100 °C, 1 atm) 42 ). In fact, Pd/C (5% Pd) catalyst 39 was totally inactive in this reaction under the conditions implemented in this study.…”
Section: Resultsmentioning
confidence: 53%
“…Deoxygenation of sulfoxides to sulfides is a fundamental and important reaction for organic synthesis and biochemistry. , The deoxygenation of sulfoxides typically requires stoichiometric amounts of reducing agents such as phosphines, boranes, silanes, and alcohols, which, however, suffer from the use of toxic reagents and the production of undesirable byproducts as well as low atom efficiency. Alternatively, the catalytic deoxygenation of sulfoxides using molecular H 2 asthe most greener reducing agent has been examined using MoO 2 Cl 2 , Pd/C, Pt-MoO x /TiO 2 , and Pt/V (1– x ) Cr x -Hol, but they require harsh reaction conditions including high H 2 pressure (>7 atm). Recently, Mitsudome et al demonstrated catalytic deoxygenation of sulfoxides under atmospheric H 2 pressure using Ru/TiO 2 at 100 °C; however, there has been no report on the deoxygenation of sulfoxides using 1 atm of H 2 at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the catalytic deoxygenation of sulfoxides with H2 represents the most environmentally friendly method for the synthesis of sulfides with high atom efficiency because water is formed as the sole by-product. [48][49][50][51][52][53] Our research group recently found that Ru/TiO2 has a high catalytic activity for the deoxygenation of various sulfoxides under ambient H2 pressure. 48 Subsequently, Pt-MoOx/TiO2, 49 Pt/V0.7Cr0.3-Hol, 50 and Pt/HxMoO3-y 51 catalysts were developed.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51][52][53] Our research group recently found that Ru/TiO2 has a high catalytic activity for the deoxygenation of various sulfoxides under ambient H2 pressure. 48 Subsequently, Pt-MoOx/TiO2, 49 Pt/V0.7Cr0.3-Hol, 50 and Pt/HxMoO3-y 51 catalysts were developed. As alternatives to expensive and rare noble-metal-based catalysts, low-cost and earth-abundant non-noble metal catalysts for the deoxygenation of sulfoxides have been also developed.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium-chromium composite oxides (VCrO) have been the subject of extensive research because of their use in a wide range of applications such as heterogeneous catalysis [1][2][3][4][5][6][7][8][9]22,23], gas sensing [24], and energy storage [25,26]. They were traditionally prepared by high-temperature solid-state reactions between pure oxide components.…”
Section: Introductionmentioning
confidence: 99%